Compounds identification through Gas Chromatography Mass Spectroscopic analysis, phytochemical screening and antioxidant properties of Ulva fasciata - S. M. Shakira Begum,; S. Dharshini, (The Bioscan, 2024)
Marine algae have been considered promising resources for new bioactive compounds in addition to their nutritional significance, multiple pharmacological, industrial, food industry, etc., activities. The Ulva fasciata is a common green alga consumed worldwide, current study focused the Ulva collected from coastal region of Ramnad, collected samples are dried made into powder, powders are dissolved in methanol and ethanol solvents then made extracts, its focused qualitative phytochemical analysis, different types of compounds identification by GC-MS analysis and free radical scavenging antioxidant activity by DPPH method. In results the crude methanol extract showed yield 0.12 g and ethanol extract showed 0.12 g yield. Qualitative analysis of methanol and ethanol extracts showed presence of tannins, saponin, cardiac glycosides, etc., GC-MS analysis of methanol extract showed 10 compounds among that the main component are glycerol tricaprylate, it showed 57.72% peak intensity and the retention time (RT) noticed 47.26, followed by 10-Nonadecanone shows 22.13% with RT 47.42, 9-Octadecenoic acid, 1,2,3-propanetriyl ester showed 2.81% peak intensity and the RT noticed 44.36. The ethanol extract showed hexadecane peak intensity 33.65% was obtained in RT 19.59, followed by hexanedioic acid, bis(2-ethylhexyl) ester showed 19.59% with the RT 42.99, azulene showed 11.88% peak intensity with RT 6.86. Methanol extract showed potential antioxidant activity 91.03% with IC50 value 284 mg/ml methanolic extract and 84.65% with IC50 value 298 mg/ml ethanolic extract, the antibacterial activity potential showed against E. coli, we concluded that methanolic extract showed potential antioxidant activity, it’s useful for pharmacological industries for human societies.